Founders : a novel of the coming collapse - Rawles, James Wesley (Atria, 2012)
In a near-future postapocalyptic world, a full-scale socioeconomic breakdown has eliminated all legal and technological infrastructure and subjected the world's survivors to constant violence and chaos.